1990
DOI: 10.1111/j.1740-8261.1990.tb00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Diagnosis of Canine Hydrocephalus

Abstract: The brains of 23 canine patients and six random-source dogs were examined ultrasonographically through the bregmatic fontanelle or a surgical craniotomy. Fifteen dogs had abnormal neurologic signs; the others were normal on neurologic examination. Untrasound results were compared with signalment, clinical signs, electroencephalography, computed tomography, radiology and histopathology. The purposes of the study were to demonstrate the use of ultrasound for the diagnosis of canine hydrocephalus and to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
17

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 29 publications
1
21
0
17
Order By: Relevance
“…Even when logistic regression models were applied, it could be noticed that there is no significant influence of the variables in the B-mode (measurements of the ventricles before and after medicine administration, presence of open fontanelle, and communication between lateral ventricles) in relation to improvement of the patient. These results confirm those previously described in the literature (Hudson et al, 1990;Spaulding and Sharp, 1990). Researches demonstrated that the acute hydrocephalus produced in cats promotes the reduction of 22% in the blood flow of the brain, cerebellum; and encephalic trunk (Hochwald et al, 1975).…”
Section: Resultssupporting
confidence: 90%
“…Even when logistic regression models were applied, it could be noticed that there is no significant influence of the variables in the B-mode (measurements of the ventricles before and after medicine administration, presence of open fontanelle, and communication between lateral ventricles) in relation to improvement of the patient. These results confirm those previously described in the literature (Hudson et al, 1990;Spaulding and Sharp, 1990). Researches demonstrated that the acute hydrocephalus produced in cats promotes the reduction of 22% in the blood flow of the brain, cerebellum; and encephalic trunk (Hochwald et al, 1975).…”
Section: Resultssupporting
confidence: 90%
“…1), sendo 16 (55,1%) fêmeas e 13 (44,9%) machos. Este resultado confirma os da literatura, sugerindo predisposição das fêmeas ao aparecimento dessa afecção (Hudson et al, 1990 (Nautrup e Tobias, 2000). As lesões focais hipoecogênicas podem ser decorrentes de hematoma, lesões granulomatosas e neoplasia (Hudson et al, 1998; Nautrup e Tobias, 2000) e as lesões hiperecogênicas, decorrentes de lesões hipóxico-isquêmicas, hemorrágicas ou neoplásicas (Hudson et al, 1998;Andrade Neto, 2004).…”
Section: Resultsunclassified
“…However, asymmetries between both LVVs were found, with the left lateral ventricle always larger than the right lateral ventricle. The asymmetry of the lateral ventricles is considered normal in healthy dogs up to a certain value [36,37,39,48,49]. In a study using Labrador retrievers, De Haan et al [37] estimated an asymmetry of 31%.…”
Section: Discussionmentioning
confidence: 99%